Wearable Fabric Reconfigurable Beam-Steering Antenna for On/Off-Body Communication System - Seonghun Kang; Chang Won Jung (International Journal of Antennas and Propagation)
This paper presents a comparison of on-body performances between omnidirectional (loop antenna) and reconfigurable beam-steering antennas. Both omnidirectional and reconfigurable antennas were manufactured on the same fabric substrate and operated at the frequency band of the WLAN 802.11a (5.725–5.85 GHz). The reconfigurable antenna was designed to steer the beam directions. In order to implement the beam-steering capability, the antenna used two PIN diodes. The maximum beam directions of three states (states 0, 1, and 2) were steerable in the YZ-plane (h=2°, 28°, and 326°, resp.). The measured peak gains were 5.9–6.6 dBi and the overall half power beam width (HPBW) was 102°. The measured results of total radiated power (TRP) and total isotropic sensitivity (TIS) indicated that the communication efficiency of the reconfigurable beam steering antenna was better than that of the loop antenna. When the input power was 0.04 W (16 dBm), the simulated specific absorption rate (SAR) values of the reconfigurable beam steering antenna on the body were less than 0.979 W/kg (1 g tissue) in all states, satisfying the SAR criteria of the US.